First spawning record of the widespread Indo-Pacific Pavona maldivensis observed in the Red Sea - Neus Garcias-Bonet; Marco Casartelli; Silvia Vimercati; Francesca Benzoni; Raquel S. Peixoto (Frontiers in Marine Science, 2025)
Information on coral reproductive biology and coral spawning times is crucial to advance basic and applied research and inform strategies for coral reef conservation and restoration. Important efforts have been made to collate coral spawning times and reproductive patterns in global and regional datasets. Here, we report and document the first in situ spawning of Pavona maldivensis Gardiner, 1905, observed in the Red Sea. A medium size colony was observed releasing sperm on the full moon night on 23 May 2024, at sunset time. Our observations suggest that the widespread Indo-Pacific P. maldivensis is likely gonochoric. This first report on the in situ spawning timing for P. maldivensis contributes to expanding coral spawning databases and provides valuable data on its reproductive biology, which is relevant for coral restoration and conservation efforts.